Improvement of thermal stability, rheological and mechanical properties of PLA, PBAT and their blends by reactive extrusion with functionalized epoxy - Al-Itry, Racha; Lamnawar, Khalid; Maazouz, Abderrahim (Polymer degradation and stability, 2012)
The aim of this study has been to gain a fundamental understanding of the mechanisms and conditions governing thermal degradation of poly (lactic acid) (PLA), poly (butylene-adipate-co-terephtalate) (PBAT) and their blends upon processing conditions. Thermal degradation of biodegradable PLA and PBAT was investigated firstly by thermal analysis and size-exclusion chromatography (SEC). It is shown that neat polymers degrade upon processing hence the decrease of the molecular weight, rheological and mechanical properties. Secondly, the reactive extrusion of polymers was performed with various amounts of chain extension/branching agent, containing nine Glycidyl methacrylate (GMA) functions, named Joncryl. The incorporation of this multi-functional oligomer showed an improvement of their thermal stability. SEC and intrinsic viscosity measurements of these modified PLA and PBAT confirmed the increase of viscosity and molecular weight probably related to the formation of extended and branched chains. Rheological investigation of extended/branched PLA and PBAT as well as their modified PLA/PBAT (80/20) (wt/wt) blends with various concentrations of GMA reactive functions exhibited higher viscosity and storage modulus compared to the unmodified samples. This increase becomes more pronounced as the concentration of Joncryl increases. Viscoelastic properties were assessed and related to the molecular structure of modified polymers. Hence, the mechanisms of degradation, chain extending with GMA functions and their competition have been proposed. The effect of reactive compatibilization on the PLA/PBAT blends has been confirmed using transmission electron microscopy (TEM), scanning electron microscopy (SEM) observations and tensile tests by the improvement of phase dispersion and the increase of both Young's modulus and strain at break.